Analysis and optimization of concentrated solar power plant for application in arid climate - Mutaz B. Elbeh (14778358) (2021)
In this research study, the concentrated solar power (CSP) technology is reviewed for designing and optimizing a CSP tower plant for arid climate regions such as Qatar. A database for all CSP projects around the world is created, and a spreadsheet model for calculating the available solar irradiance is developed. Two software packages are used for analyzing and optimizing the entire solar thermal plant and its cost, SolarPILOT, and System Advisor Model (SAM). Both packages are validated using data from a recent power tower project. A thorough iterative optimization process was developed and applied to optimize the solar field parameters of a suggested CSP plant including tower optical height; heliostat structure width and height; number of heliostats; horizontal and vertical panels; receiver height and diameter; water consumption; cleaning schedule; maintenance; and total cost. The results confirmed the feasibility of a CSP plant on 0.45 km2 of a solar field area with 2736 heliostats that produce 8 MWe with 10 hours of thermal storage and hybrid steam condensing system. It has been found that the highest production of the plant is in July, which is 3 621 950 kWh and the highest excess of electrical energy is in March, which is 2 946 965 kWh. Other Information Published in: Energy Science & Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ese3.742